(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
This paper analyzes the way the Italian Constitutional Court decides about technical and scientific questions. The analysis is developed from a double point of view: on the one hand, the paper deals with the substantial element of the content of the most important decisions, and, on the other hand, it analyzes the features of constitutional trial in case of technical and scientific issues.